Medical Device–Related Hospital-Acquired Pressure Ulcers: Development of an Evidence-Based Position Statement. Issue 2 (March 2015) - Pittman, Joyce; Beeson, Terrie; Kitterman, Jessica; Lancaster, Shelley; Shelly, Anita
Abstract : Hospital-acquired pressure ulcers (HAPUs) are a problem in the acute care setting causing pain, loss of function, infection, extended hospital stay, and increased costs. In spite of best practice strategies, occurrences of pressure ulcers continue. Many of these HAPUs are related to a medical device. Correct assessment and reporting of device-related HAPUs were identified as an important issue in our organization. Following the Iowa Model for Evidence-Based Practice to Promote Quality Care, a task force was created, a thorough review of current evidence and clinical practice recommendations was performed, and a definition for medical device-related HAPU and an evidence-based position statement were developed. Content of the statement was reviewed by experts and appropriate revisions were made. This position statement provides guidance and structure to accurately identify and report device-related HAPU across our 18 healthcare facilities. Through the intentional focus on pressure ulcer prevention and evidence-based practice in our organization and the use of this position statement, identification and reporting of device-related HAPUs have improved with a decrease in overall HAPU rates of 33% from 2011 and 2012. This article describes the development and implementation of this device-related HAPU position statement within our organization.